2016
DOI: 10.1186/s12909-016-0704-3
|View full text |Cite
|
Sign up to set email alerts
|

Understanding students’ readiness for interprofessional learning in an Asian context: a mixed-methods study

Abstract: BackgroundHealthcare is generally provided by various health professionals acting together. Unfortunately, poor communication and collaboration within such healthcare teams often prevent its members from actively engaging in collaborative decision-making. Interprofessional education (IPE) which prepares health professionals for their collaborative role in the healthcare system may partially address this problem. This study aimed to investigate: 1) students’ readiness for IPE in an Asian context, 2) the most im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
74
3
17

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 36 publications
6
74
3
17
Order By: Relevance
“…It was noted in the focus groups and the literature that physicians were at 'the top of the hierarchy' and other healthcare professionals' contributions were perceived to be marginalised (Lestari, Stalmeijer, Widyandana, & Scherpbier, 2016). This is similar to another study where pharmacy students blamed physicians for their status and, as a result handed power and status back to the physicians (Layzell, 2012).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…It was noted in the focus groups and the literature that physicians were at 'the top of the hierarchy' and other healthcare professionals' contributions were perceived to be marginalised (Lestari, Stalmeijer, Widyandana, & Scherpbier, 2016). This is similar to another study where pharmacy students blamed physicians for their status and, as a result handed power and status back to the physicians (Layzell, 2012).…”
Section: Discussionsupporting
confidence: 70%
“…It is essential that healthcare students are mentored by exemplary role models during their educational experience, value IPC and effectively communicate with the healthcare team to improve the quality of patient care (Curran et al, 2008;Lestari et al, 2016). Also, students require IPE opportunities to develop the competencies needed for them to be valued members contributing to healthcare teams (Curran et al, 2008).Students observed collaboration in some hospitals in Qatar and hence these environments can be targeted for pharmacy placements to offer the students the chance to observe collaboration in practice.…”
Section: Discussionmentioning
confidence: 99%
“…(26) Chua et al also found higher baseline RIPLS scores for medical undergraduates compared to other groups of undergraduates, a nding also noted in this study and another done in a culturally similar country. (26,29) This is contrary to other studies which found that medical students had a lower RIPLS score. (30,31) Chua et al also found that prior exposure to IPE resulted in signi cantly higher RIPLS scores.…”
Section: Discussioncontrasting
confidence: 93%
“…Lestari et al, state that medical students are the readiest on the understanding of professional identity and role on collaboration compare with the other students like nurse, midwife and dentistry students. 10 Professional identity is important aspect on IPE implementation. 11 The lecturers and curriculum team in this research was agreed that IPE development is necessary to be implemented.…”
Section: Medical and Midwiferymentioning
confidence: 99%